NMDA receptor activation underlies the loss of spinal dorsal horn neurons and the transition to persistent pain after peripheral nerve injury - Inquimbert, Perrine; Moll, Martin; Latremoliere, Alban (Cell reports, 2018)
Peripheral nerve lesions provoke apoptosis in the dorsal horn of the spinal cord. The cause of cell death, the involvement of neurons, and the relevance for the processing of somatosensory information are controversial. Here, we demonstrate in a mouse model of sciatic nerve injury that glutamate-induced neurodegeneration and loss of γ-aminobutyric acid (GABA)ergic interneurons in the superficial dorsal horn promote the transition from acute to chronic neuropathic pain. Conditional deletion of Grin1, the essential subunit of N-methyl-d-aspartate-type glutamate receptors (NMDARs), protects dorsal horn neurons from excitotoxicity and preserves GABAergic inhibition. Mice deficient in functional NMDARs exhibit normal nociceptive responses and acute pain after nerve injury, but this initial increase in pain sensitivity is reversible. Eliminating NMDARs fully prevents persistent pain-like behavior. Reduced pain in mice lacking proapoptotic Bax confirmed the significance of neurodegeneration. We conclude that NMDAR-mediated neuron death contributes to the development of chronic neuropathic pain.
Gesehen am 17.02.2020